ผลของดีคาร์บอกซีเลชั่นของกรดอะมิโนร่วมกันในการปรับปรุงอาหารไฮโดรเจนซัลไฟด์สำหรับการตรวจวิเคราะห์ซัลโมเนลลากลุ่มที่สามารถรีดิวซ์ไทโอซัลเฟตเบื้องต้น (COMBINED EFFECT OF AMINO ACID DECARBOXYLATION ON THE IMPROVEMENT OF HYDROGEN SULFIDE ENRICHMENT MEDIA FOR PRESUMPTIVE SCREENING OF THIOSULFATE – REDUCING SALMONELLA ) - หิรัณย์สร, พิมพ์นิภา; สาระนาค, จุรีพรรณ; ดีพัฒนา, อาณัติ; ทิพยรัตน์, อาลักษณ์ (Srinakharinwirot University Journal of Sciences and Technology, 2020)
The food industry needs rapid and reliable methods that are convenient and cost-effective as primary screens for routine inspections of Salmonella spp. contamination. To fulfil Salmonella screening step, hydrogen sulfide (H2S) indicator medium was proposed and tested in a microwell plate. Method: The combined effect of amino acid decarboxylation on the increase of black precipitation, H2S indicator broth (TFX) plus with lysine-ornithine (TFXLO), ornithine-arginine (TFXOA), or lysine-arginine (TFXLA) were studied in seven H2S+ Salmonella serovars and thirteen non-salmonellae Salmonella and non-salmonellae to improve hydrogen sulfide production and black precipitation contrast. The TFX broth containing lysine (TFXL) was compared as control. The black precipitates, as indicator of the reaction were followed by optical density (OD650) changes and visualization. Result: Different supplement with combined amino acids provided different ferrous sulfide precipitates and OD650 signals depending on Salmonella serovars. The black precipitates of all typical Salmonella had improved with more contrast in all combined amino acids, especially ornithine-arginine based broth (OD650=1.7–2.5), compared to single lysine usage (OD650=1.4–2.1). Thiosulfate-ferric ammonium citrate system commonly provided ineffective results for black precipitates in atypical Salmonella (Salmonella Anatum and Salmonella Typhi). The lysine-arginine combined effect could fix the low H2S contrast OD650 from 0.9 to 1.6 in S. Anatum. However, none of combined amino acids was able to improve hydrogen sulfide production in atypical S. Typhi. All H2S enrichment media could differentiate all non-thiosulfate reducing salmonellae competitors tested out of Salmonella. There was no differentiation of three H2S+ Salmonella competitors from Salmonella in any media, except Citrobacter freundii in TFXL broth. Conclusion: The selected ornithine and arginine as the nutrient base was noted for further improvement in hydrogen sulphide reaction system. With applying H2S indicator media alternative to conventional selective broths, the total detection time for presumptive results was shortened; more rapid than conventional protocol for up to 48 h.